Country Economic Memorandum for Sao Tome and Principe - Background Note 7 : What are the Bottlenecks on Land Governance and How to Remove Them to Support Tourism and Agriculture Development? - Moreno Horta, Ivonne; Pardo, Camilo (World Bank, Washington, DC, 2019)
This note explores land governance-related constraints holding back the growth potential of the agriculture and tourism sectors in the Democratic Republic of São Tomé and Príncipe (STP). The absence of a proper land information system and a weak land governance framework are identified as the major constraints to rural development and tourism. This note provides insights, identifies the most salient weaknesses, and presents recommendations to address these issues. The first section describes the history of land tenure in the country. The second section focuses on the positive impacts that the establishment of a land information system can have for rural development and the tourism sectors and describes the institutions in charge of land management and related legislation. The fourth section identifies the main inefficiencies in land administration affecting economic growth. The final sections outline the activities currently in execution to address such issues and present policy recommendations.